Effect of ZrO2 nano-particles on mechanical and corrosion behaviour of Al2024 alloy. (2021) - Kennedy, Edward; Sachin, B.S.; Ramachandra, M.; Niranjan, C.A.; Sriraman, N.; Jain, Vikram Kumar S.; Sathiya Narayanan, N.
Abstract: In this study, mechanical and corrosion behaviour of aluminium 2024 (Al-2024) alloy reinforced with varying weight percentage (0, 2, 4 and 6%) of ZrO2 nanoparticles have been investigated. The composite was prepared through stir casting route. The composite samples were subjected to indentation measurement. The electrochemical polarization test was carried out in 3.5% NaCl solution (seawater environment) to evaluate the corrosion resistance of the composites in comparison with alloy. The corrosion resistance of the composites is significantly increased in a seawater environment due to the addition of ZrO2 nanoparticles. The corrosion morphology of the samples after corrosion was examined using the scanning electron microscope.